Religious Hegemony and Authoritarian Resilience: The Case of Morocco - Elewa, Shaza (AUC Knowledge Fountain, 2021)
Religious hegemony is a common strategy that is enacted by Arab regimes to retain their power over society. The case of Morocco is an interesting case, since it has its specific religious status due to the claimed linkage between the ruling dynasty and the prophet of Islam (Daadaoui 2013, 27). This religious dominance over the Moroccan political and civil spheres reflects the neo-Gramscian theory introduced by Mouffe and Laclau (Gramsci 1971, Laclau and Mouffe 1985, Bocock 1986). Through examining this theory, this thesis demonstrates how the Moroccan monarchy reacted to the 20th of February Movement that erupted in 2011 during the Arab Uprisings through employing a religious hegemonic discourse as part of the announced political reforms to maintain the monarchy's hold on power.